PENGARUH KUALITAS PEGAWAI TERHADAP PRESTASI KERJA PADAKANTOR DINAS TATA RUANG KABUPATEN KUTAI TIMUR - Paisal Paisal (ADMINISTRASI PUBLIK, 2017)
Tokknow whether the quality of civil employees have positive and significant impact on the achievements of the work Dinas Pengendalian Lahan dan tata Ruang Kabupaten Kutai Timur. The data collected through the questioner by 40 respondents servants of Dinas Pengendalian lahan Dan tata Ruang Kabupaten Kutai Timur. The data collected were analyzed by simple Linear Regression tests using the program SPSS for windows. Data analysis results show that the quality of government employees have positive and significant impact on the achievements of the work in Dinas Pengendalian Lahan Dan tata Ruang Kabupaten Kutai Timur, after known R count 0,604 > R table of 0,312, and the value of the significance of 0.000 smaller than 0.05. The value of R Square of 36.5 percent, it means that the quality of the employees could affect the achievements of Work of Dinas Pengendalian Lahan dan tata Ruang Kabupaten Kutai Timur 36.5 percent, while the remaining 63.5 percent influenced by other variables which are not examined in this research.